Coronary artery bypass grafts and diagnosis related groups: Patient classification and hospital reimbursement in 10 European countries - James Gaughan; Conrad Kobel (Health Economics Review, 2014)
Background: The prospective reimbursement of hospitals through the grouping of patients into a finite number of categories (Diagnosis Related Groups, DRGs), is common to many European countries. However, the specific categories used vary greatly across countries, using different characteristics to define group boundaries and thus those characteristics which result in different payments for treatment. In order to assist in the construction and modification of national DRG systems, this study analyses the DRG systems of 10 European countries. Aims: To compare the characteristics used to categorise patients receiving a coronary artery bypass graft (CABG) surgery into DRGs. Further, to compare the structure into which DRGs are placed and the relative price paid for patients across Europe. Method: Patients with a procedure of CABG surgery are analysed from Austria, England, Estonia, Finland, France, Germany, Ireland, Poland, Spain and Sweden. Diagrammatic algorithms of DRG structures are presented for each country. The price in Euros of seven typical case vignettes, each made up of a set of a hypothetical patient's characteristics, is also analysed for each country. In order to enable comparisons across countries the simplest case (index vignette) is taken as baseline and relative price levels are calculated for the other six vignettes, each representing patients with different combinations of procedures and comorbidities. Results: European DRG payment structures for CABG surgery vary in terms of the number of different DRGs used and the types of distinctions which define patient categorisation. Based on the payments given to hospitals in different countries, the most resource intensive patient, relative to the index vignette, ranges in magnitude from 1.37 in Poland to 2.82 in Ireland. There is also considerable variation in how much different systems pay for particular circumstances, such as the occurrence of catheterisation or presence of comorbidity. Conclusion: Past experience of the construction of DRG systems for CABG patients demonstrates the variety of options available. It also highlights the importance of updating systems as frequently as possible, to incentivise best practice.
Keywords: 330; Diagnosis-related groups; DRGs; Hospital financing; Coronary artery bypass graft; CABG; Reimbursement